Reasons for Students Interest in Learning Physics Subjects in Senior High School - Kurniawan, Affandi Faisal; Ristanto, Sigit; Khoiri, Nur (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2023)
The purpose of this study was to identify the reasons of students' interest in learning physics in Senior High School. This type of research is descriptive qualitative. The data collection method used includes a questionnaire. The questionnaire is in the form of closed questions with a Likert scale from 1-5 addressed to students. This research was conducted in local schools in the city of Semarang that were selected in accordance with the direction and objectives of this research. School A represents superior schools, school B represents mediocre schools, and school C represents non-excellent schools.The results showed that 1) the highest percentage of interest in learning physics was at School A which was 78.72%. Meanwhile, the lowest percentage of interest in learning physics is 46.83% (School C). The percentages are 67.59%, 56.76%, and 55.56%, respectively.